Upstream Foreclosure Decisions under Successive Monopoly Structure†. (9th September 2014) - Chongvilaivan, Aekapol
Abstract : This article models the upstream foreclosure decisions using the successive monopoly structure, whereby production requires two types of inputs, exclusive materials, and commonly available labor. An opportunity for upstream foreclosure arises when a downstream firm strategically merges with the material supplier, thereby foreclosing its rival's access to the exclusive input. The model shows that upstream foreclosure is not always optimal. A downstream firm opts for upstream foreclosure only when its relative positions in the labor‐management and material‐procurement negotiations are sufficiently strong. Copyright © 2014 John Wiley & Sons, Ltd.